Reduction in total plasma ghrelin levels following catecholamine depletion: Relation to bulimic and depressive symptoms - Homan, Philipp; Grob, Simona; Milos, Gabriella; Schnyder, Ulrich; Hasler, Gregor (Psychoneuroendocrinology, 2013)
There is increasing preclinical and clinical evidence of the important role played by the gastric peptide hormone ghrelin in the pathogenesis of symptoms of depression and eating disorders. To investigate the role of ghrelin and its considered counterpart, peptide tyrosine tyrosine (PYY), in the development of bulimic and depressive symptoms induced by catecholamine depletion, we administered the tyrosine hydroxylase inhibitor alpha-methyl-paratyrosine (AMPT) in a randomized, double-blind, placebo-controlled crossover, single-site experimental trial to 29 healthy controls and 20 subjects with fully recovered bulimia nervosa (rBN). We found a decrease between peprandial and postprandial plasma ghrelin levels (p<0.0001) and a postprandial rise in plasma PYY levels (p<0.0001) in both conditions in the entire study population. Plasma ghrelin levels decreased in the entire study population after treatment with AMPT compared to placebo (p<0.006). AMPT-induced changes in plasma ghrelin levels were negatively correlated with AMPT-induced depressive symptoms (p<0.004). Plasma ghrelin and plasma PYY levels were also negatively correlated (p<0.05). We did not observe a difference in ghrelin or PYY response to catecholamine depletion between rBN subjects and healthy controls, and there was no correlation between plasma ghrelin and PYY levels and bulimic symptoms induced by catecholamine depletion. These findings suggest a relationship between catecholamines and ghrelin with depressive symptoms.